PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING PADA MATA PELAJARAN IPA KELAS V SD NEGERI 05 JAYAPURA KABUPATEN SIAK - Witri, Gustimal; Rusli, Rusli; Harzuliana, Nur Three; Akmalia, Zeti (Jurnal Manajemen Pendidikan, 2021)
This study aims to determine the application of the Blended Learning Model in science subjects for class V SD 05 Jayapura. The subjects of this study were 5th grade students who found 30 students consisting of 13 male students and 17 female students. This study aims to determine the differences in students' science learning outcomes before and after the application of the Blended Learning learning model. The method used in this research is experiment. This research was conducted for 30 days, where the first day gave the students a pretest, the second day until the 29th day gave learning, and the 30th day was a posttest. The results of the study were seen from the students' pretest and posttest. In the pretest results of 30 students, there are 14 students who have completed and 16 other students who have not completed with an average of 62.16. Then in the posttest the number of students who have completed has increased, namely 27 people, while students who have not completed, namely 3 people, are obtained so that the average is 77.16 which is quite high. The results of the t-test with t-count = 12,281 and t-table = 2,045, it can be said that tcount> ttable, then Ho is rejected and Ha is accepted. Mixed Learning